Characterization and classification of agricultural soils in North Savo, Finland - Yli-Halla, Markku; Räty, Mari (Luonnonvarakeskus, 2024)
Information of soil properties is commonly needed in agricultural research. Experimental sites need to be documented in order to understand the factors influencing the results as well as to extrapolate the information to areas of similar soils. Soil data is used in modelling soil and environmental processes. Topsoil properties are usually obtained through agricultural soil testing but for comprehensive soil description deeper soil horizons need also to be analysed. Pedogenic soil classification according to international systems, such as the World Reference Base for Soil Resources (WRB), a system endorsed by the EU, is needed to put the soils into an international context. In this study, altogether 21 soil profiles were investigated in Maaninka and Iisalmi in North Savo, Finland. The selected sites are used for field experiments carried out in North Savo by the Natural Resources Institute Finland (Luke). The sites were investigated in the field by excavating a soil pit to the depth of 1–1.5 m. The soil profile was morphologically described and photographed. Soil samples were taken by the horizon and analysed for relevant properties. The profiles were classified by the WRB system (IUSS Working Group WRB 2022). On the basis of the morphological and analytical results, the most pronounced pedogenic soil processes of the area were identified and the common soil types in agricultural use were recognized. Almost all pedons had a horizon consisting of clay or clay loam within the investigated depth. It is obvious that these fine- and medium-textured soil materials are spread out throughout the agricultural soils of the area. Glacial till was rarely found in the fields. The plough layer was loamy in most soils. These clayic and fine loamic layers were at some sites covered with sandy esker material. The base saturation was usually above 50% indicating the abundance of weatherable minerals. All soils exhibited signs of wetness. Some pedons had brown redox concentrations and gray redox depletions only in the subsoil but in some other soils the redoximorphic features were observed right below the plough layer, while wetness and saturation with water has been the prerequisite of the formation of peat soils. Many soils had illuvial material on subsoil aggregate surfaces. In most soils there was a varved appearance in the subsoil below the frost depth, indicating negligible pedogenic development. It is noteworthy that no morphological signs of podzolization were observed. Altogether, six out of the 32 main soil classes of the WRB system were recorded in the area: Histosols (2 pedons), Gleysols (4), Planosols (6), Stagnosols (4), Arenosols (1) and Regosols (4). These soil classes indicate wetness and negligible pedogenic soil development.
Keywords: agricultural soils; mineral soils; peat soils; pedogenesis; soil analysis; soil classification; soil morphology